KEWAJIBAN PENJUAL MENYERAHKAN HEWAN KURBAN YG DIBELI SECARA ONLINE SESUAI DENGAN YG DIPERJANJIKAN DI KOTA PONTIANAK - NIM. A1011161164, FARAZETIARA FADILLAH (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACT In addition, the improving economy is also a factor in increasing community participation in the sacrifice. Apart from cows, buffaloes and sheep, goats are animals that can be used as sacrificial animals during the Eid al-Adha holiday. This is because the price of goats is quite cheap and affordable compared to cows and buffalo. Goats are also classified as commercial slaughter animals, their meat is loved by almost all levels of society. Yahya Farm Farm has 150 goat kurban animals that are ready to be sold to buyers online. This indicates that goat livestock does not only play a role in the implementation of sacrificial and slaughter animals, but can also function as savings and additional income by the people of Kubu Raya Regency in running the economy. Goat livestock also has several advantages and economic potential, including relatively easy maintenance, does not require large areas of land, relatively small business capital investment, and is easy to market so that business capital rotates quickly.So the authors can formulate this research problem as follows: